Enhancing Brand Quality through Business Kit Assistance for Micro Enterprise Jamu Bandung - Arissaputra, Rivaldi; Sentika, Sarah; Sena Rahma Amelia (CV. AFDIFAL MAJU BERKAH, 2023)
This project addresses the challenges faced by micro 'Jamu Bandung' enterprises in Indonesia. The background of the project highlights the significance of these small businesses in preserving traditional herbal medicine practices and the need to adapt to modern market dynamics. The research methodology employed a qualitative approach, including interviews, surveys, document analysis, and observation, to improve the impact of branding, packaging design, and e-commerce strategies. The results of this project have provided invaluable insights, as follows: (1) Implementation of comprehensive Brand Guidelines has significantly improved brand consistency within the micro 'Jamu Bandung' sector, fostering a unified brand identity and instilling trust among consumers, (2) Innovative packaging designs have substantially increased the appeal of 'Jamu Bandung' products. Detailed analyses demonstrate the specific design elements contributing to consumer attraction and market success, (3) The integration of e-commerce strategies shows promise in expanding market reach and deepening customer engagement. A detailed exploration of these strategies and their impact on consumer behavior offers a nuanced understanding of the project's effectiveness. Future endeavors in this direction should prioritize addressing digital literacy challenges and ensuring the sustainability of these enhancements. These efforts are crucial for long-term success and the continued preservation of Indonesia's herbal medicine heritage.